Analysis of Theacher’s Role in Utilization of Chemistry Laboratory at School - Samiun, Moh Ilpan; Nuryanti, Siti (Media Eksakta, 2022)
This study aims to (1) describe the teacher's role in the use of the chemistry laboratory (2) describe the teacher's obstacles in the use of the chemistry laboratory (3) describe the solution to overcome the obstacles in the use of the chemistry laboratory. This research uses descriptive qualitative research with an inductive approach. This research uses observation, interview, and documentation techniques. The results of the study show: (1) the role of the teacher as a class manager develops students' abilities in using learning tools, provides conditions that allow students to work and learn, the teacher as a facilitator provides facilities that allow students to learn optimally to get poor results. good. (2) the main obstacles are inadequate facilities and infrastructure, namely insufficient tools and materials, lack of teacher time allocation and lack of teacher readiness. (3) the solution is to provide alternative tools and materials, hold a meeting again with the principal to discuss the completeness of tools and materials, discuss the allocation of teacher time, and provide input so that the person in charge of the laboratory and chemistry teachers can be included in the chemical laboratory management training.